Extremely Cost‐Effective and Efficient Solar Vapor Generation under Nonconcentrated Illumination Using Thermally Isolated Black Paper. Issue 2 (30th January 2017) - Liu, Zhejun; Song, Haomin; Ji, Dengxin; Li, Chenyu; Cheney, Alec; Liu, Youhai; Zhang, Nan; Zeng, Xie; Chen, Borui; Gao, Jun; Li, Yuesheng; Liu, Xiang; et al.
Abstract : Solar vapor generation with no electrical input is a promising and environmentally benign solution, and has become a topic of increasing interest in recent years. Here, an efficient system utilizing extremely low‐cost carbon‐based material is developed to realize simultaneous vapor generation and water purification to produce drinking water for personal use. This is particularly attractive for addressing global freshwater shortages. Abstract : Passive solar vapor generation represents a promising and environmentally benign method of water purification/desalination. However, conventional solar steam generation techniques usually rely on costly and cumbersome optical concentration systems and have relatively low efficiency due to bulk heating of the entire liquid volume. Here, an efficient strategy using extremely low‐cost materials, i.e., carbon black (powder), hydrophilic porous paper, and expanded polystyrene foam is reported. Due to the excellent thermal insulation between the surface liquid and the bulk volume of the water and the suppressed radiative and convective losses from the absorber surface to the adjacent heated vapor, a record thermal efficiency of ≈88% is obtained under 1 sun without concentration, corresponding to the evaporation rate of 1.28 kg (m 2 h) −1 . When scaled up to a 100 cm 2 array in a portable solar water still system and placed in an outdoor environment, the freshwater generation rate is 2.4 times of that of a leading commercial product. By simultaneously addressing both the need for high‐efficiency operation as well as production cost limitations, this system can provide an approach for individuals to purify water for personal needs, which is particularly suitable for undeveloped regions with limited/no access to electricity.